Cord Blood Cell-Free DNA Concentration: A Novel Marker for Neonatal Wellbeing - Imterat, Majdi; Erez, Offer; Tirosh, Dan; Gelkop, Yael Miller; Benshalom-Tirosh, Neta; Ben-Tabo, Maor; Douvdevani, Amos (American Journal of Perinatology, 2022)
Objective Cord gas values and Apgar scores, currently used as markers for newborn wellbeing and postpartum complications, provide rough estimates, and their use remains elusive. Circulating cell-free DNA (cfDNA) may better represent newborn status at birth and the effect of parturition on the fetus. This pilot study investigates the association between cord blood (CB) cfDNA and neonatal outcomes.Study Design In a prospective cohort study, cfDNA concentration was measured in immediately following delivery collected CB sera of newborns using our rapid fluorescent assay.Results During the study period, blood samples from umbilical cords of 100 newborns were collected. Vaginal delivery was associated with a higher median CB cfDNA than cesarean delivery (277 [95% confidence interval [CI] 199–377] vs. 100 [95% CI 43–265] ng/mL, p < 0.01). cfDNA levels were significantly associated with gestational age at delivery (rho = 0.308, p = 0.002) and CB base deficit (BD, r = 0.252, p = 0.017). According to maternal and fetal complications, CB cfDNA was elevated in fetuses with category II of heart rate tracing (p < 0.05), with maternal positive vaginal culture (p < 0.01), and with premature rupture of membranes (PROM, p < 0.001). Logistic regression models of CB cfDNA fourth quartiles demostrate a double odds ratio for elevated BD (>3mmol/L) and for worse heart rate tracing category.Conclusion Serum CB cfDNA concentration reflects the newborn's status and hazards with an excellent association with CB BD, fetal heart rate category, and maternal risk factors for infection (positive vaginal culture and PROM). This preliminary observation suggests that cfDNA can serve as a point of care biomarker for newborn status at the time of delivery.Key Points
Keywords: Circulating cell-free DNA; neonatal morbidity; neonate; birth; delivery; pregnancy